Retromer subunit, VPS29, regulates synaptic transmission and is required for endolysosomal function in the aging brain - Ye, Hui; Ojelade, Shamsideen A; Li-Kroeger, David; Zuo, Zhongyuan; Wang, Liping; Li, Yarong; Gu, Jessica YJ; Tepass, Ulrich; Rodal, Avital Adah; Bellen, Hugo J; Shulman, Joshua M (eLife, 2020)
Retromer, including Vps35, Vps26, and Vps29, is a protein complex responsible for recycling proteins within the endolysosomal pathway. Although implicated in both Parkinson’s and Alzheimer’s disease, our understanding of retromer function in the adult brain remains limited, in part because Vps35 and Vps26 are essential for development. In Drosophila, we find that Vps29 is dispensable for embryogenesis but required for retromer function in aging adults, including for synaptic transmission, survival, and locomotion. Unexpectedly, in Vps29 mutants, Vps35 and Vps26 proteins are normally expressed and associated, but retromer is mislocalized from neuropil to soma with the Rab7 GTPase. Further, Vps29 phenotypes are suppressed by reducing Rab7 or overexpressing the GTPase activating protein, TBC1D5. With aging, retromer insufficiency triggers progressive endolysosomal dysfunction, with ultrastructural evidence of impaired substrate clearance and lysosomal stress. Our results reveal the role of Vps29 in retromer localization and function, highlighting requirements for brain homeostasis in aging.
Keywords: VPS29; VPS35; Drosophila; endolysosomal trafficking; TBC1D5; Rab7